PHYTOCHEMICAL ANALYSIS OF ETHANOLIC EXTRACT OF LEAVES OF CLITORIA TERNATEA L. - R. KAVITHA; V. PREMALAKSHMI (International Journal of Pharma and Bio Sciences, 2013)
Medicinal plants are of great importance to the health of individuals and communities. A large number of plants are claimed to possess the anti-diabetic, anti-fertility, anti-hyperlipidaemic, anti-inflammatory, anti-cancer, hepatoprotective and immunomodulatory activities in the traditional therapeutic systems. It is now believed that nature has given the cure of every disease in one way or another. Clitoria ternatea a valuable medicinal plant possess many bioactive principles which includes diabetes mellitus, chronic bronchitis, goitre, mucous disorders and leprosy. The ethanolic extract of leaves of C.ternatea was investigated for its phytochemical properties and analysis for its active chemical ingredients. For qualitative and quantitative phytochemical analysis the ethanol extract of C.ternatea acts as a source of therapeutic agent.